Reconciling the use of technology in investigations with fundamental rights: the case of monitoring of public and private spaces - Jacqueline de Souza Abreu; Gianluca Martins Smanio (Revista Brasileira de Direito Processual Penal)
Technological advances offer tools to law enforcement authorities that must be reconciled with the protection of fundamental rights. This article discusses the compatibilization process of one of these tools: the case of interception of optical, acoustic and electromagnetic signals in public and private spaces. This tool is briefly mentioned in Brazilian law, present only in the article 3, II, of the Law n.º 12.850/2013. As an evidence gathering method, known for its secrecy and invasiveness, it is of the most importance to restrain its use with more detailed laws that reconcile the tool with fundamental rights. In order to contribute to this process, this article reviews how this monitoring tool has been incorporated into Brazilian law and discussed in scholarship. Next, in light of the lessons of the European Court of Human Rights, a provision found in the recent “Anti-crime” bill that would further incorporate the tool in Brazilian law is critically discussed.